(3ePcQGJ JGQjNjI efJNHI ef cJGH GdEMGWI aj CNHGQ ZQfGWI hZjQgG ef JhGQjN GdCfOdSs - (3CMeO Rci HGTGs; (3CHhYHO Gddg eMeO Hf YHO Gddg Hf SYjO GdSdeGfi GdZQfGWi GdCfOdSj, GdTgjQ HdSGf GdOjf Hf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3hef Pdc eG UOQ Yfi ai eaGNQI eGdbI hSdG , HeG fUg s
(3BNQgG (B:s
(3GdeGFI GdKGdKI , hef Hfi GdCZdH Hf CHj GdCZdH hGSeg GdfM s
(3hGdfSNI ecJhHI HGdbde GdQUGUs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B235s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B382 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs